Cranes among chickens: The general-attention‐grabbing effect of daily price limits in China's stock market - LIN, Fengjiao; QIU, Zhigang; ZHENG, Weinan (Journal of Banking & Finance, 2023)
This paper examines the general-attention-grabbing effect of daily price limits in China's stock market. We show that stocks with large exposure to daily price limits attract more investor attention and have lower future returns. The exposure is measured empirically through the absolute beta with respect to the daily proportion of stocks that hit price limits. The general-attention-grabbing effect is not solely caused by stocks that recently hit price limits, is not subsumed by market volatility exposure, and does not reflect other stock market characteristics. Moreover, the effect is stronger among stocks that are heavily invested in by retail investors.